Profiling of Differentially Expressed MicroRNAs in Saliva of Parkinson's Disease Patients - Jiang, Yanyan; Chen, Jing; Sun, Yunchuang; Li, Fan; Wei, Luhua; Sun, Wei; Deng, Jianwen; Yuan, Yun; Wang, Zhaoxia (Frontiers in Neurology, 2021)
Objective: This study aims to identify differentially expressed salivary miRNAs and validate the diagnostic potential for idiopathic Parkinson’s disease (PD). Also, the disease specificity of candidate miRNAs was evaluated between PD, multiple system atrophy (MSA), and essential tremor (ET). Methods: We collected salivary samples from 50 PD, 20 ET, and 20 MSA patients, as well as 30 healthy controls (HCs). In the discovery phase, salivary miRNA microarray analysis was performed. In-silico analysis was used to investigate the target genes of differentially expressed miRNAs and clustered pathways. In validation phase, RT-qPCR was performed with samples from 30 PD patients and 30 HCs. Subsequently, we investigated candidate miRNAs in all recruited subjects. Receiver operating characteristic curve and Spearman correlation analysis was performed to determine diagnostic usefulness. Results: We identified 34 miRNAs that were differentially expressed between 5 PD patients and 5 HCs by miRNA microarray analysis. Computational analysis revealed the target genes were clustered in the pathways associated with ubiquitin protein ligase activity. The result of RT-qPCR showed that the miR-29a-3p and miR-29c-3p were found to be significantly downregulated (p=0.004, p=0.027), whereas the miR-6756-5p was significantly upregulated in 30 PD patients compared with 30 HCs (p=0.032). The miR-29a-3p expression level in PD patients was significantly lower than ET patients (p=0.035), but higher than MSA patients (p<0.0001). The diagnostic efficacy reached a little higher when the combination of miR-29a-3p and miR-29c-3p. Conclusion: The miRNA combination of salivary miR-29a-3p and miR-29c-3p has potential to be a diagnostic biomarker for idiopathic PD.